Psychosocial treatments targeting anxiety and depression in adolescents and adults with autism spectrum disorder: Review of the latest research and recommended future directions - White, Susan W. (Curr Psychiatry Rep, 2018)
PURPOSE OF REVIEW. This synthesis of treatment research related to anxiety and depression in adolescents and adults with autism spectrum disorder (ASD) focuses on the support for various forms of psychosocial interventions, useful adaptations to standard interventions, and engagement of candidate therapeutic mechanisms. RECENT FINDINGS. There is considerable evidence for the efficacy of cognitive-behavioral therapy (CBT) to treat co-occurring problems with anxiety, in the context of relatively little research on treatment of co-occurring depression. Multiple mechanisms of treatment effect have been proposed, but there has been little demonstration of engagement via experimental therapeutics. SUMMARY. Comorbidity between ASD and anxiety and/or mood problems is common. Although there is evidence for the use of CBT for anxiety, little work has addressed how to effectively treat depression. There is emerging support for alternative treatment approaches, such as mindfulness-based interventions. We encourage rigorous, collaborative approaches to identify and manipulate putative mechanisms of change.